A comparative study of drying methods on physical characteristics, nutritional properties and antioxidant capacity of broccoli. Issue 10 (1st July 2020) - Xu, Yayuan; Xiao, Yadong; Lagnika, Camel; Song, Jiangfeng; Li, Dajing; Liu, Chunquan; Jiang, Ning; Zhang, Min; Duan, Xu
Abstract: Broccoli is considered one of the attractive raw materials for dehydrated vegetables owing to its high nutritional value. However, information about how drying methods affect the physicochemical and nutritional properties of broccoli is limited. In this study, broccoli pieces were subjected to freeze drying (FD), hot air drying (HAD), microwave vacuum drying (MVD), vacuum drying (VD), MVD combined with HAD (MVD + HAD), and MVD combined with VD (MVD + VD). Quality attributes of dehydrated broccolis were contrasted in terms of color, texture, volume shrinkage, nutritional components, antioxidant activity, and rehydration capacity. Results demonstrated that FD better preserved the nutrients while HAD displayed the worst effect. The combination of MVD + HAD and MVD + VD resulted in higher retention of nutritional compositions, better antioxidant activity, and lower energy consumption than that of HAD. Furthermore, combined drying processing exhibited similar rehydration capacity but lower hardness compared to that of HAD.